Originarios y forasteros del sur andino en el período colonial - Castro Olañeta, Isabel (2016)
Long term research project on the movements of the indigenous populations of Chichas, Tarija and Tucumán (17th and 18th centuries), which, for the period prior to the Bourbon reforms, experiences great difficulty comparing and integrating disparate information. In the 17th century, Chichas and Tarija were recipients of indigenous populations originating in the broad region that spans from Cuzco to Tucumán. Studying the same process as seen from Tucumán at the end of the 18th century shows that the population movements reversed: Tucumán ceased to be an ejector of significant indigenous populations toward Chichas and Tarija and instead became a recipient of populations originating in these same places, a situation that indicates the existence of population groups that move within a common area and according to a set of circumstances.